2009
DOI: 10.1080/08927010903096008
|View full text |Cite
|
Sign up to set email alerts
|

The serine protease Esperase HPF inhibits the formation of multispecies biofilm

Abstract: The antifouling (AF) potential of the serine protease Esperase HPF (subtilisin) was evaluated for the ability to prevent the formation of a four-species bacterial biofilm. The effects of enzyme activity, time and application of the enzyme were tested on the density and the oxidative metabolism of biofilm developed in microtiter wells. Esperase HPF did not inhibit the oxidative metabolism of the bacterial biofilm or planktonic growth, but the enzyme inhibited biofilm formation by its proteolytic activity as ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…D41 (Leroy et al 2008b). In contrast, the enzyme inhibitory effects were comparable to the detachment effects for a multispecies biofilm (Hangler et al 2009) suggesting that, in this case, the enzyme effectively degrades both protein-based adhesives and proteins contained in the matrix (Hangler et al 2009). Recent work also showed that differences in chemical composition of the EPS are reflected on the vulnerability of biofilms to enzymatic treatment (Lequette et al 2010;Chaignon et al 2007;Augustin et al 2004).…”
Section: Insert Figurementioning
confidence: 92%
“…D41 (Leroy et al 2008b). In contrast, the enzyme inhibitory effects were comparable to the detachment effects for a multispecies biofilm (Hangler et al 2009) suggesting that, in this case, the enzyme effectively degrades both protein-based adhesives and proteins contained in the matrix (Hangler et al 2009). Recent work also showed that differences in chemical composition of the EPS are reflected on the vulnerability of biofilms to enzymatic treatment (Lequette et al 2010;Chaignon et al 2007;Augustin et al 2004).…”
Section: Insert Figurementioning
confidence: 92%
“…D41, suggesting its ineffectiveness on structural composition of the biofilm matrix. In contrast, Hangler et al [15] observed that the serine protease Esperase HPF (subtilisin) affected both the attachment and the detachment of a multispecies biofilm, suggesting that, in this case, the enzyme effectively degraded both protein-based adhesives and proteins contained in the matrix. Recent work also showed that differences in the chemical composition of the EPS are reflected in the vulnerability of biofilms to enzymatic treatments [2,7,25].…”
Section: Resultsmentioning
confidence: 87%
“…One Gram positive bacterium namely Microbacterium phyllosphaerae and three Gram negative bacterial strains namely, Shewanella japonica, Dokdonia donghaensis and Acinetobacter lwoffii were all isolated from green alga Ulva australis. The effects of time and amount of Esperase HPF, was tested on the robustness and the oxidative metabolism of biofilm developed in 96 well plates [30]. Esperase HPF did not inhibit the oxidative metabolism of the bacterial biofilm or inhibit planktonic growth, but the enzyme inhibited biofilm formation by its proteolytic activity and heat inactivated enzyme had no effect.…”
Section: Use Of Commercially Available Proteases As Antibiofilm Agentsmentioning
confidence: 99%
“…The antifouling (AF) potential of the serine protease Esperase HPF (subtilisin) was evaluated by Hangler et al [30] for its ability to prevent the biofilm formation of a four-species bacterial species. One Gram positive bacterium namely Microbacterium phyllosphaerae and three Gram negative bacterial strains namely, Shewanella japonica, Dokdonia donghaensis and Acinetobacter lwoffii were all isolated from green alga Ulva australis.…”
Section: Use Of Commercially Available Proteases As Antibiofilm Agentsmentioning
confidence: 99%
See 1 more Smart Citation